Long-term chipping and failure rates of implant-supported and combined tooth-implant-supported metal-ceramic and ceramic fixed dental prostheses: a cohort study - Rammelsberg, Peter; Meyer, André; Lorenzo Bermejo, Justo; Kappel, Stefanie; Zenthöfer, Andreas (The journal of prosthetic dentistry, 2021)
Statement of problem - Combined tooth-implant-supported fixed dental prostheses have been associated with an increased risk of long-term failure. Furthermore, high chipping rates have been reported for ceramic fixed dental prostheses. However, clinical data are sparse. - Purpose - The purpose of this observational cohort study was to evaluate the chipping and failure rates of metal-ceramic and ceramic implant-supported and combined tooth-implant-supported fixed dental prostheses. - Material and methods - Four hundred thirty-four fixed dental prostheses placed in 324 patients (mean age: 60.8 years) were selected from a prospective clinical long-term study comprising 213 implant-supported fixed dental prostheses, 66 implant-supported cantilever fixed dental prostheses, and 155 tooth-implant-supported fixed dental prostheses. Metal-ceramic fixed dental prostheses (n=260) were fabricated with a high noble metal alloy (n=225) or Co-Cr base metal alloy (n=35) frameworks. Ceramic fixed dental prostheses (n=174) were all zirconia based and had monolithic (n=68), completely veneered (n=43), or partially veneered frameworks (n=63). Kaplan-Meier curves were used to estimate the survival probability and the chipping-free survival rate of the fixed dental prostheses. - Results - During the observation period of 0.5 to 12.6 years (mean: 4.26 years), 17 fixed dental prostheses failed because of implant failure (n=6), tooth loss (n=5), major chipping (n=5), or abutment screw loosening (n=1). Survival probability was 96% after 5 years and 91% after 10 years. Cox regression analysis showed that age, sex, fixed dental prosthesis location, type of fixed dental prosthesis support, and fixed dental prosthesis material had no significant effect on fixed dental prosthesis failure. Chipping (n=61) was significantly affected by the framework material and type of veneer (P=.001). After 5 years, the greatest incidence of chipping (39%) was observed for zirconia fixed dental prostheses with a complete veneer compared with an 18% incidence of chipping for metal-ceramic fixed dental prostheses with a high noble metal framework. A lower incidence of chipping was observed for zirconia fixed dental prostheses with a partial veneer or monolithic design. - Conclusions - Implant-implant-supported and combined tooth-implant-supported fixed dental prostheses have promising long-term survival rates. Chipping seems to occur less frequently in monolithic or partially veneered fixed dental prostheses than in fixed dental prostheses with complete veneers.
Available online 14 August 2020
Gesehen am 08.09.2021